METODE PENYADARAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI SMKN 1 BONE - Asse, Muhammad; S., Samsinar (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Basically, the Islamic education awareness method is very effective in fostering the personality of students. This paper aims to reveal the meaning of the awareness method and the types of awareness methods applied by teachers at SMKN 1 Bone. This research includes field research and is located at SMKN 1 Bone. Data were collected using observation guidelines, interview guides and document searches as well as relevant journal articles and books. The results showed that the Islamic education awareness method is very effective in fostering the personality of students and motivating them so that the application of this method allows tens of thousands of believers to open human hearts to receive divine guidance and Islamic civilization concepts. The method of awareness of Islamic education essentially contains three integral dimensions, which cannot be separated from one another. The three dimensions are awareness aimed at human nature as monotheistic creatures (tawhid) and faith in God, direction aimed at lust and guidance aimed at reason as the power of reason. From the three dimensions above, it can be seen that the subjects and objects of da'wah are humans.Islamic Religious Education teachers at SMKN 1 Bone have formulated several methods to make students aware. Summing up five effective and influentive educational methods, namely; Awareness method with exemplary, habits, advice, attention, and punishment.